1998
DOI: 10.1073/pnas.95.4.1840
|View full text |Cite
|
Sign up to set email alerts
|

Anin vitroblood–brain barrier model: Cocultures between endothelial cells and organotypic brain slice cultures

Abstract: This communication describes a novel in vitro blood-brain barrier (BBB) model: organotypic slice cultures from the central nervous system were overlaid on endothelial cell monolayers grown on permeable membranes. Morphological, electrophysiological, and microdialysis approaches were carried out to characterize and validate this model. After 10 days in coculture, morphological studies reveal the presence of tight junctions. Electrophysiological recordings of neuronal activity performed on organotypic cultures w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(40 citation statements)
references
References 72 publications
1
38
0
1
Order By: Relevance
“…However, the complexity of the geometry (multiple hollow fi bres) in this model, and the assumptions made in calculating TEER from the current measured, make it diffi cult to compare TEER values with those from fl at fi lter confi gurations. Generation of more-complex 3-D cultures has also been reported (Duport et al 1998 ;Hatherell et al 2011 ). However, tri-culture, DIV and 3-D models are more diffi cult to set up and maintain than standard mono or co-cultured models (Fig.…”
Section: Tri-culture Dynamic Flow and 3-d Modelsmentioning
confidence: 90%
“…However, the complexity of the geometry (multiple hollow fi bres) in this model, and the assumptions made in calculating TEER from the current measured, make it diffi cult to compare TEER values with those from fl at fi lter confi gurations. Generation of more-complex 3-D cultures has also been reported (Duport et al 1998 ;Hatherell et al 2011 ). However, tri-culture, DIV and 3-D models are more diffi cult to set up and maintain than standard mono or co-cultured models (Fig.…”
Section: Tri-culture Dynamic Flow and 3-d Modelsmentioning
confidence: 90%
“…The other cell types present at the BBB, including pericytes, perivascular macrophages, and neurons, also contribute to barrier induction (Duport et al 1998, Ramsauer et al 2002, Zenker et al 2003. Given the complexity of the BBB properties and the anatomical relationship of the associated cell types, it is not surprising to find synergistic inductive functions involving more that one cell type.…”
Section: Blood-brain Barrier In the Vertebratesmentioning
confidence: 99%
“…In 1998, Duport et al (1998) reported a coculture consisting of cortical organotypic slice cultures (COSCs) and BECs and validated this model using electrophysiological recordings and electron microscopy. However, an extensive study of BBB properties under physiologic and pathophysiological conditions would benefit from the application of additional techniques, such as immunohistochemistry (IHC), fluorescent live cell imaging, and electrical cell substrate impedance sensing (ECIS, which is a validated marker for barrier integrity in real time).…”
Section: Introductionmentioning
confidence: 99%